Armazenamento de sementes e produção de mudas de Parapiptadenia rigida (Benth.) Brenan - Gasparin, Ezequiel (2012)
Parapiptadenia rigida (angico-vermelho) is a native forest specie with wide natural distribution in the Brazilian territory, mainly used for rural construction, firewood and charcoal, and play a key role in forest restoration. Nevertheless, there are few studies and predatory exploitation of this specie undertakes preservation and perpetuation. The present study aimed to evaluate the influence of storage at different storage conditions and packages on the physiological quality of seeds, and investigate the effect of containers level and doses of controlled release fertilizers (FLC) on growth seedling grown in nurseries and performance in the field. The seeds were collected from 28 trees in Santa Maria (RS) and, after processed, was identified the most suitable substrate for the conduct of the germination test. Then, the seeds were stored in three conditions (cold chamber, refrigerator and laboratory environment), packed in three types of package (paper, plastic and glass) for a period of 420 days. Periodically, samples were taken of these conditions to evaluate the physiological quality of seeds. In the nursery stage, was examined the effects of five doses of FLC, NPK (05-18-09) at doses of 0 (control), 3, 6, 9 and 12 g L-1 substrate, combined with three volumes of containers (50, 110 and 180 cm3). Evaluations were made of the height (H), stem diameter (DC), H/DC, dry mass of shoot, root and total, and macro and micronutrient content of the shoots. The same treatments were evaluated under field, during a period of 300 days, verifying the rate of initial survival and measured to H, DC and calculated the H/DC. The results showed that the germination test can be conducted using the substrate of sand in, with initial count of seedlings to four days and the final ten days after sowing. The seed storage in the refrigerator and package paper was the most appropriate storage for 420 days and can also use plastic and glass in the same condition. For the production of seedlings with standard for planting it, is recommended the level of 9 g L-1 of substrate in container of 180 cm3. In the post-planting, this container has high performance, regardless of the levels of FLC, which increased linearly in time due to depletion of the FLC in the substrate and likely leaching of nutrients.